The myths’ exegesis in Plotinus and Porphyre - Oliveira, Loraine (Revista Archai, 2010)
In Plotinus the myths are scattered throughout the Enneads”Ÿ treatises. In contrast with Porphyry, Plotinus prefers to make allusions and fragmentary quotations of the myths rather than an exegesis of a comprehensive extract of a poem. Only one of Porphyry”Ÿs works, dedicated to the allegorical exegesis of Homer, has come down to us in its integrity: The cave of the Nymphs in the Odyssey. In this work, which is studied here, Porphyry follows a complete extract of Homer in order to find a hidden meaning beneath the letter of the text. Through an analysis of a small sample of the plotinian mythical kaleidoscope and then of Porphyry”Ÿs above-mentioned work, this article intends to show the main characteristics of the mythical exegesis of the epical tradition in both authors.myth, exegesis, image, genealogy, allegory.